A Review of Expert System Applied in Real Estate Valuation - Prita Kusuma Ahmad Borhannuddin, Justine; Hadi Haji Nawawi, Abdul; Ezwan Mohd Sofian, Edie; ., . (International Journal of Engineering and Technology, 2018)
Expert system application is found in various industries, especially in real estate, medical, law, engineering and social science. The complexity of the real estate environment demands a technology like expert system that able to automating a process for valuing a property and produces an estimated value to the real estate market participants. However, the expert system is not a common in property valuation practice in Malaysia as compared to in developed countries such as the United State America and the United Kingdom. The purpose of this paper is to explore the expert system and its implementation in real estate valuation. By exploring the expert system, the limitation and benefits of the expert system in real estate valuation are also identified. Expert system has ability to solve complex problems of property valuation. Thus, expert system shall be practicable by real estate valuers in Malaysia to ensure the reliable valuation is delivered.Â Â